Towards an understanding of public decision making a pragmatic study of the Field-Based Investigation (FBI) of the National Commission on Indigenous Peoples (NCIP) for the application of Philippine Mining Development Corporation (PMDC) - Neri, Krisna Athena C.
This study was conducted to identify the speech acts employed in the utterances during the Filed-Based Investigation proceeding conducted by NCIP in response to PMDC's application and to know how these utterances and speech acts contributed to the decision making of the Mansaka tribe of Maco, Compostela Valley Province. With the permission of NCIP, the researcher attended the FBI proceeding on January 30, 2008 and recorded the process. These recorded data were transcribed into text and used as the major data of this study. Based from the text, the speech acts were identified using Bach and Harnish's (2008) version on speech acts. And in knowing its contribution to the decision of the IP's Deetz's (Griffin, 2006) and Hirokawa's (cited by Barge, 2008) concepts on a good decision making were applied. The analyses of the study were divided into two parts: first, the analysis on the speech acts employed in the utterances; and, second, how these utterances and speech acts contributed to the IPs' decision making. The first part of the analysis is divided into three major activities? first part, discussion, second part discussion and the interview. Using Hirokawa's and Deetz's concepts, it was revealed that the first activity provided ample information to the IPs but was low in involvement and participation. The speaker from NCIP did all the talking as the rest while the participants remained quiet as they listened. The second part was high in involvement, participation is fairly neither high nor low; while the information from NCIP was limited. However, the third part was low in participation, high in involvement and the interview provided sufficient information to the NCIP team. Only the ranking of the frequently used speech acts was presented in the second part of the analysis. Information was found to be very important in the FBI process. It was evident in the result wherein speakers communicate to provide information, ask for information and disclose personal information and opinion. These were ranked as the top three methods frequently employed in the process. In the whole study, the researcher was able to find that these key concepts ? understanding, interests which are freely and openly expressed and interaction ? were vital components of a good decision making for Ips.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication